Implementation of a centralised aminoglycoside monitoring service. (June 2015) - O'Hara, Kate; Prior, Felicity H.; Whyte, Ian M.
Abstract Following the Therapeutic Guidelines: Antibiotic recommendation for computerised dose monitoring for aminoglycosides, there was a need for health services to implement these systems. We describe the establishment of a centralised aminoglycoside monitoring service designed to be accessible across the local health district. The service was established within the local medicines information service, and uptake and acceptance of recommendations were reviewed at 12 months. The service was well accepted following the first 12 months, although uptake was low. The implementation of the service was considered to be a successful addition to practice and to the local health district.